USE AND EFFECTIVENESS OF NIGERIAN STORED PRODUCTS RESEARCH INSTITUTE DISSEMINATED TECHNOLOGIES AMONG FARMERS IN KWARA STATE, NIGERIA - Kayode, A. O.; Adeniyi, A. F.; Williams, P. G.; Bello, O. G. (Journal of Agripreneurship and Sustainable Development, 2022)
Reducing post-harvest losses (PHL) offers a more cost-effective and environmentally sustainable way to promote food and nutrition safety than focusing solely on increased productivity. This study assessed the use and effectiveness of NSPRI disseminated storage technologies among grain crop farmers. Specifically, it identified the NSPRI storage technologies available to grain crops farmers; examined the availability of the NSPRI technologies; examined the extent of use of the technologies; assessed farmers’ perception of the effectiveness of the technologies; and identified constraints to the use of the technologies. A two-stage random sampling procedure was used to select 130 farmers on whom questionnaire was administered. Data collected was analyzed using descriptive statistics, multiple regression and Pearson’s product moment correlation. The extent of use of storage technologies was low (MS = 1.16) though farmers used fumigant most (MS = 1.55). The farmers perceived that NSPRI dust was the most effective among the disseminated technologies. Availability (MS = 2.68) and lack of technical know-how (MS = 2.66) were the major constraints to the use of the technologies. At P<0.01, age (β = -0.004), household size (β=-0.019), years of education (β = 0.186) and frequency of contact with extension agents (β = 0.330) were the socio-economic determinants of the use of the technologies. Availability, and type of grain cultivated also influenced the use and type of technology used. The study concluded that the use and effectiveness of the disseminated NSPRI technologies among grain crop farmers was low. Availability was identified as the major constraint to the use of the technologies. It was recommended that the technologies should be made available at open markets or through extension agents at affordable costs for easy accessibility by the farmers.